Consumer Demand for Fresh Marine Fish in Peninsular Malaysia - Abu Samah, Kamaruzzaman (1987)
The general objective of the study was to examine the consumer demand for fresh marine fish in Peninsular Malaysia. In particular, the study aimed at evaluating the important factors in determining the demand for fish, estimating elasticity values, as well as projecting the demand up to the year 2000. Two models were used, a single equation and a simultaneous equation. A single equation model was us ed in the demand analysis of fish by species and grades, whereas, the demand for total fish was evaluated by the simultaneous equation demand model. To estimate the empirical models, annual data from the period of 1950 to 1984 was used. A single equation which was in the form of price dependent model was estimated by using Ordinary Least Squares (OLS) and Cochrane-Orcutt iterative techniques, whereas, the simultaneous model was estimated by Two Stage Least Squares (2SLS). It was found that the important variables in the single equation model were income per capita, average price index of fish and meat, trend and quantity of fish consumed per capita. The results suggest that fresh marine fish can be either normal, inferior, substitutes or complementary commodity depending on the specific areas of the study. A similar situation was observed with the own price elasticity of fresh marine fish.